2021
DOI: 10.1590/0037-8682-0511-2020
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of accidents involving venomous animals in the State of Ceará, Brazil (2007-2019)

Abstract: Introduction: Envenomation remains a neglected public health problem in most tropical countries. Epidemiological studies on accidents caused by venomous animals are scarce in the Northeast region of Brazil, mainly in the state of Ceará. The present study aimed to describe the epidemiological features of envenomation cases involving venomous animals in the State of Ceará, Northeastern Brazil, from 2007 to 2019. Methods: The online Notifiable Diseases Information System was consulted for data on all envenomation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
16

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
0
6
0
16
Order By: Relevance
“…The majority of the cases were mild (94.6%), with 4.5% of the cases being moderate and 0.9% severe. Other studies have also reported a higher incidence of mild cases in several regions of Brazil, while severe cases varied from 0.4% to 13.5% [10][11][12][13] . Envenoming with T. serrulatus registered in Santa Catarina did not evolve severely, which can be associated with the lower number of cases with children in this state, since other states show a higher prevalence in children aged 0-12 years old [10][11][12][13][14][15][16] and T. serrulatus is involved in most severe cases and fatal outcomes, especially when the victims are children 17 .…”
Section: Discussionmentioning
confidence: 80%
“…The majority of the cases were mild (94.6%), with 4.5% of the cases being moderate and 0.9% severe. Other studies have also reported a higher incidence of mild cases in several regions of Brazil, while severe cases varied from 0.4% to 13.5% [10][11][12][13] . Envenoming with T. serrulatus registered in Santa Catarina did not evolve severely, which can be associated with the lower number of cases with children in this state, since other states show a higher prevalence in children aged 0-12 years old [10][11][12][13][14][15][16] and T. serrulatus is involved in most severe cases and fatal outcomes, especially when the victims are children 17 .…”
Section: Discussionmentioning
confidence: 80%
“…Diversos estudos têm mostrado maior incidência de escorpionismo em mulheres ocupadas em serviços domésticos 5,18,29,34,36,37 . Entretanto, estudos realizados no Extremo Sul da Bahia 20 , Vitória da Conquista-BA 33 e Jequié-BA 38 demonstraram que a maioria dos casos de escorpionismo ocorreu em homens (70,1%) que exerciam atividade de produção no meio rural, sugerindo que o ambiente pode influenciar diretamente no perfil do acidentado por escorpionismo.…”
Section: Discussionunclassified
“…This type of accident is frequent and represents a serious public health issue in tropical countries. 1 In Brazil, accidents involving venomous animals are compulsory notification events since 2010, and those caused by snakes, scorpions, spiders, and caterpillars are of priority interest for the epidemiological surveillance system. 2 Overall, these accidents are more serious in children than in adults, 3 considering that the amount of injected venom is independent of the victim's age and the unbound fraction concentration in organs is higher in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%